Arsenic, Lead and Cadmium contamination and pH analysis of skincare cosmetics found in Nepalese market - Basnet, Shishir; Shrestha, Sulochana; Pathak, Arvind (Scientific World, 2025)
Cosmetics are skin and hair care materials used to beautify and enhance appearance, and the demand for cosmetics is increasing rapidly. The increased consumption of cosmetic products to nurture skin poses the problem of the presence of excessive heavy metals and their impact on consumers. This research aimed to assess the levels of arsenic (As), lead (Pb), cadmium (Cd), and pH in five different popular cosmetic creams currently available in the Nepalese market. The lead and cadmium concentrations were determined by Atomic Absorption Spectroscopy (AAS), while the continuous hydride generation method determined the arsenic concentration. The pH of the products was measured using a digital pH meter. The analysis indicated that lead concentrations ranged from 8.93±0.027 to 27.18±0.030 ppm, among which just one sample (PDS-04) concentration was within the acceptable level of 10 ppm which is recommended by ISO/TR 17276. Cadmium concentration varied between non-detectable to 1.22±0.010 ppm, within the permissible limits. The arsenic contamination was not detectable. The pH was found highest at 8.7 in FH-01 and lowest in samples HM-03 and PDS-04.